Alfred Marshall and current thought - Pigou, A.C. (London : Macmillan & Co Ltd., 1955)
The first part of this book reproduces with a few modifications the Marshall lectures for 1953 given in the University of Cambridge. The second part consists of a statistic-economic paper on Problems of the Trade Balance.
Includes bibliographical footnotes.
rpm 27/10/2017
Loans
Keywords: Marshall, Alfred; Economics; Politics